Income effects and the welfare consequences of tax in differentiated product oligopoly - Rachel Griffith; Lars Nesheim; Martin O'Connell (Centre for Microdata Methods and Practice (cemmap), 2015)
Random utility models are widely used to study consumer choice. The vast majority of applications make strong assumptions about the marginal utility of income, which restricts income effects, demand curvature and pass-through. We show that flexibly modeling income effects can be important, particularly if one is interested in the distributional effects of a policy change, even in a market in which, a priori, the expectation is that income effects will play a limited role. We allow for much more flexible forms of income effects than is common and we illustrate the implications by simulating the introduction of an excise tax.
Keywords: L13; H20; 330; income effects; compensating variation; demand estimation; oligopoly; pass-through